AB0570 Association between sledai-2k domains and organ damage accrual. (12th June 2018) - Zhang, K.; Boyd, S.; Petitjean, F.; Hoi, A.; Koelmeyer, R.; Morand, E.; Nim, H.
Abstract : Background: Prevention of permanent organ damage is a key goal of SLE management1. Overall disease activity measured by SLE Disease Activity Index (SLEDAI-2k) is a risk factor for damage2, but the contribution of organ-specific activity to damage risk has not been enumerated. Objectives: We sought to determine the degree to which organ domains of SLEDAI-2k are associated with damage accrual. Methods: A dataset of SLE patients (2007 – 2017) at the Australian Lupus Registry was studied. Variables collected at each visit included all domains of SLEDAI-2k, Physician Global Assessment, and medications. Systemic Lupus International Collaborating Clinics/ACR Damage Index (SDI) was recorded annually and each visit was labelled "damage transition" or "non-damage transition" based on whether SDI increased at the subsequent annual measure. The association of risk of SDI increase with SLEDAI-2k domains was assessed using multivariable logistic regression analysis adjusted for confounding by medication use. Results: 5538 visits from 266 patients (86.5% female, 47.4% Caucasian, 66% dsDNA positive) were analysed; at enrolment median (range) SLEDAI-2k was 4 (0–26) and SDI was 0 (0–4 ). Upon multivariable regression analysis, domains found to be significant were: low complement, proteinuria, haematuria, leukopenia, pyuria, pericarditis, alopecia, rash and arthritis. Upon further adjustment for prednisolone exposure, the effects of some domains were attenuated, but pericarditis (odd ratio (OR)=4.06, 95%CI=1.68–9.83), pyuria (OR=1.94, 1.47–2.56), arthritis (OR=1.71, 1.35–2.16), and rash (OR=1.43, 1.20–1.70), alopecia (OR=1.43, 1.10–1.86) and leukopenia (OR=1.36, 1.03–1.78) remained significant. No other SLEDAI-2k domains showed a significant association, in part due to infrequent occurrence. SLEDAI-2k domains weightings were not congruent with the respective risk of damage accrual. Conclusions: In study, only some SLEDAI-2k domains were significantly associated with organ damage accrual. Re-appraisal of weightings in SLE disease activity scores based on their association with outcome is potentially warranted. References: [1] Van Vollenhoven RF, Mosca M, Bertsias G, et al. Treat-to-target in systemic lupus erythematosus: recommendations from an international task force. Annals of the rheumatic diseases2014:annrheumdis-2013. [2] Bruce IN, O'Keeffe AG, Farewell V, et al. Factors associated with damage accrual in patients with systemic lupus erythematosus: results from the Systemic Lupus International Collaborating Clinics (SLICC) Inception Cohort. Annals of the rheumatic diseases2015;74(9):1706–13. Disclosure of Interest: None declared